Rethinking the fifth discipline : learning within the unknowable - Flood, Robert L. (Routledge, 1999)
This text aims to make improvements to the core discipline of systemic thinking. It establishes developments in this area in the context of the learning organization, including organizational transformation. An introduction to the gurus of systemic thinking is also featured.